KORELASI KECEMASAN INTRAPARTUM KALA I FASE AKTIF PRIMIGRAVIDA DENGAN DURASI DILATASI SERVIKS PERSALINAN NORMAL: Correlation of Intrapartum Anxiety in First Stage Active Phase of Primigravida with Duration of Cervical Dilatation in Normal Labor - Solichatin, Solichatin; Khoirul Waroh, Yuni (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
ABSTRACT Normal delivery is the process of expelling the fetus from the mother's womb with the mother's own strength. In normal delivery, the baby comes out through the birth canal and causes the mother's body to experience physiological changes, one of which is cervical dilatation. Women, especially primigravida mothers who are approaching the time of delivery, experience psychological changes that can affect labor. most notably as anxiety. This study aims to determine the influence of anxiety in primigravida mothers on cervical dilatation during normal delivery. The method used was cross-sectional with data coming from a questionnaire to measure the mother's anxiety level and secondary data in the form of a partograph to measure the duration of cervical dilatation. The population selected in this study were primigravida mothers who give birth normally at term at TPMB Yefi Marliandiani Rungkut Surabaya. The sampling technique used was consecutive sampling, namely during the first stage of the active phase of primigravida with cervical dilatation of 4 cm, totaling 34 respondents. The data obtained was analyzed to determine the effect of the independent variable on the dependent variable using a simple linear regression test. This type of qualitative research uses an analytical design and a cross sectional approach. The analysis used is univariate with a frequency distribution and bivariate using a simple linear regression test. The results of the study showed that there was an influence of 27.9% of the anxiety level of primigravida mothers on the duration of cervical dilatation during normal delivery at TPMB Yefi Marliandiani Kata kunci: Intrapartum Anxiety, Active Phase, Primigravida, Cervical Dilatation ABSTRAK Persalinan normal adalah sebuah proses keluarnya janin dari rahim ibu dengan kekuatan ibu sendiri. Pada persalinan normal, bayi keluar melalui jalan lahir dan menyebabkan tubuh ibu mengalami perubahan fisiologis, salah satunya adalah dilatasi serviks. wanita terutama ibu primigravida yang mendekati waktu persalinan mengalami perubahan psikologis yang dapat mempengaruhi persalinan. terutama kecemasan. Penelitian ini bertujuan untuk mengetahui adanya pengaruh dari kecemasan ibu primigravida terhadap dilatasi serviks pada persalinan normal. Metode yang digunakan cross-sectional dengan data berasal dari kuesioner untuk mengukur tingkat kecemasan ibu dan data sekunder berupa partograf untuk mengukur durasi dilatasi serviks. Populasi yang dipilih dalam penelitian ini adalah ibu primigravida yang melahirkan secara normal aterm di TPMB Yefi Marliandiani Surabaya. Teknik Sampling adalah Consecutive sampling, yaitu inpartu kala I fase aktif primigravida dengan dilatasi serviks 4 cm sebanyak 34 responden. Data yang diperoleh dianalisis untuk mengetahui pengaruh variabel bebas terhadap variabel terikat menggunakan uji regresi linier sederhana. Jenis penelitian kualitatif dengan desain analitik dan pendekatan cross sectional Analisis yang digunakan adalah univariat dengan distribusi frekuensi dan bivariat menggunakan uji regresi linier sederhana. Hasil penelitian menunjukkan bahwa terdapat pengaruh sebesar 27,9% dari tingkat kecemasan ibu primigravida terhadap durasi dilatasi serviks pada persalinan normal di TPMB Yefi Marliandiani Keywords: Kecemasan Intrapartum, Fase Aktif, Primigravida, Dilatasi Serviks